Inter-laboratory study on the detection of bovine processed animal protein in feed by LC-MS/MS-based proteomics. (July 2021) - Lecrenier, Marie-Caroline; Marien, Aline; Veys, Pascal; Belghit, Ikram; Dieu, Marc; Gillard, Nathalie; Henrottin, Jean; Herfurth, Uta M.; Marchis, Daniela; Morello, Sara; Oveland, Eystein; Poetz, Oliver; et al.
Abstract: Since the beginning of the feed ban regarding the use of processed animal protein (PAP) in feedstuffs, one of the main challenges has been to develop methods to detect and identify the type and origin of PAP or animal products. By now, in the context of a controlled relaxation of the ban, complementary methods are sought to characterize the product when positive responses are delivered by current official methods, with special attention on feed materials (whether or not authorized) originating from ruminants. Liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based proteomics was identified as the most promising method to meet this challenge. This study presents the first inter-laboratory test constructed to evaluate and compare the LC-MS/MS methods currently developed in six different laboratories from four countries. Nine samples consisting of blank feed matrix or feed adulterated with bovine processed animal proteins and/or milk products were analyzed using in-house protocols and the results obtained were discussed. This study confirms the potential of LC-MS/MS-based proteomics to resolve the current analytical gaps in the detection and differentiation of PAP and highlights the technical challenges that need to be addressed in future. Graphical abstract: Image 1 Highlights: Complementary analytical methods are necessary for effective feed ban control. MS-based proteomics is a promising emerging approach for feed analyses. Comparison of complementary MS methods developed in six laboratories. Results are of interest to further improvement and refinement of feed control.